2017
DOI: 10.1021/acs.jpcc.7b08512
|View full text |Cite
|
Sign up to set email alerts
|

Design of Roughened Current Collector by Bottom-up Approach Using the Electroplating Technique: Charge–Discharge Performance of a Sn Negative-Electrode for Na-Ion Batteries

Abstract: The use of high capacity electrode materials based on alloying and dealloying reactions with Na is very effective for improving energy density of batteries. However, their application brings on electrical isolation such as detachment of the electrode mixture layer from a current collector, causing rapid capacity fading. We previously found that Cu electrochemically grows in sheet form by electroplating in a CuSO4-based aqueous solution with poly­(acrylic acid) (PAA). In the present study, our goal was to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Electrochemical reactivities of SnO and SnO 2 with potassium were studied by galvanostatic charge–discharge cycling test with 2032-type coin cells and cyclic voltammetry measurements with three-electrode cells at 25 °C. For comparison, Sn powder with a diameter of 70–500 nm was used . Reaction mechanism was investigated by means of ex situ X-ray diffraction (XRD, SmartLab; Rigaku) with CuKα radiation, ex situ Raman spectroscopy (T64000; HORIBA, Ltd.), and X-ray photoelectron spectroscopy (XPS; PHI Quantera II, ULVAC-PHI, Inc.) with an X-ray (monochromatic radiation Al–Kα) beam diameter of 100 μm operated at 25 W. XPS spectra were calibrated using the binding energy of hydrocarbon (C–C, C–H groups) at 284.6 eV.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical reactivities of SnO and SnO 2 with potassium were studied by galvanostatic charge–discharge cycling test with 2032-type coin cells and cyclic voltammetry measurements with three-electrode cells at 25 °C. For comparison, Sn powder with a diameter of 70–500 nm was used . Reaction mechanism was investigated by means of ex situ X-ray diffraction (XRD, SmartLab; Rigaku) with CuKα radiation, ex situ Raman spectroscopy (T64000; HORIBA, Ltd.), and X-ray photoelectron spectroscopy (XPS; PHI Quantera II, ULVAC-PHI, Inc.) with an X-ray (monochromatic radiation Al–Kα) beam diameter of 100 μm operated at 25 W. XPS spectra were calibrated using the binding energy of hydrocarbon (C–C, C–H groups) at 284.6 eV.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…However, because the raw material of Li is localized in South America, the manufacturing always faces resources constraint. There is no doubt that the issue becomes more and more serious with the popularization of electric vehicles, and this is also the motivation for the development of Na-ion batteries (NIBs). Furthermore, recently, a rechargeable battery based on reversible uptake/release of K ion as the charge carrier has been considered. Despite the larger size than Na ion, the electrochemical intercalation of K ion into graphite was demonstrated by Jian et al: ex situ XRD studies clarified that the formation of KC 8 by stepwise potassiation from KC 36 delivered a reversible capacity of 273 mA h g –1 .…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for the popularization of autonomous vehicles. Li-ion batteries are still the most promising energy storage devices and have been widely used in portable devices as well as large-scale systems although Na ion, K ion, Mg ion, Ca ion, and Al ion have been considered carrier ions from the perspective of not being free from resource constraints. As innovation in electrode materials is needed for the further improvement of energy density, Si has been attracting a great deal of attention as an alternative to graphite (LiC 6 : 372 mA h g –1 ) currently used as a negative electrode material for conventional Li-ion batteries. This is motivated by the relatively low operation potentials and a significantly large theoretical capacity of 3580 mA h g –1 (Li 15 Si 4 ) based on lithiation and delithiation reactions. , However, Si has the disadvantage of a poor cycle life because the active material layer is isolated from an electrical network in the electrode due to the pulverization suffered from an extremely large volume change by 280% during alloying and dealloying with Li. In addition to this, the low Li + diffusion coefficient (10 –15 to 10 –10 cm 2 s –1 ) , and the low electrical conductivity (∼10 5 Ω cm) disallow the exploitation of the potential high capacity, which is one of the bottlenecks in the practical application of Si negative electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, a joining technology with a roughened plating film that does not rely on composite plating is desirable. We have already reported that a roughened electrodeposited copper film can be fabricated using a roughening agent [19], and that the roughened copper film acts as an effective current collector when applied to a lithium [20,21] or sodium [22] ion battery anode.…”
Section: Introductionmentioning
confidence: 99%